Quantification of stress-induced mitogen-activated protein kinase expressional dynamic using reverse transcription quantitative real-time PCR - Křenek, Pavel; Smékalová, Veronika (Methods in molecular biology, 2014)
Although it is generally accepted that signal transduction in plant mitogen-activated protein kinase signaling cascades is regulated via rapid posttranslational modifications, there are also several compelling examples of swift stress induced transcriptional activation of plant MAP kinase genes. A possible function of these fast and transient events is to compensate for protein losses caused by degradation of phosphorylated MAP kinases within stimulated pathways. Nevertheless, there is still need for additional evidence to precisely describe the regulatory role of plant MAP kinase transcriptional dynamics, especially in the context of whole stress stimulated pathways including also other signaling molecules and transcription factors. During the last two decades a reverse transcription quantitative real-time PCR became a golden choice for the accurate and fast quantification of the gene expression and gene expression dynamic. In here, we provide a robust, cost-effective SYBR Green-based RT-qPCR protocol that is suitable for the quantification of stress induced plant MAP kinase transcriptional dynamics in various plant species.
Keywords: Stress, Physiological; RNA rostlin; chlorid sodný; Sodium Chloride; Osmotic Pressure; osmotický tlak; Arabidopsis; DNA primery; regulace genové exprese u rostlin; mitogenem aktivované proteinkinasy; semenáček; DNA Primers; kvantitativní polymerázová řetězová reakce; Reverse Transcription; Cloning, Molecular; reverzní transkripce; Real-Time Polymerase Chain Reaction; fyziologický stres; DNA, Complementary; Seedlings; RNA, Plant; komplementární DNA; Gene Expression Regulation, Plant; klonování DNA; Mitogen-Activated Protein Kinases